Gardens of the Old Gods: Ecocriticism of Yggdrasil in the Eddas - Renger, James (CSUCI Journal of Undergraduate Research, 2013)
The Prose Edda and the Poetic Edda serve as the primary texts from which we draw our modern understanding of ancient Norse mythology. Central in these myths is the role of nature, which is depicted in a ways that are closely associated with contemporary understandings of the world in which we live, and there is no better demonstration in of the ecological concepts in these tales then Ygdrasil. By understanding the ecological connections in ancient Norse mythology through the Ygdrasil imagery, it is possible to make the eco-critical analysis of the mythology while shedding light on the very real contemporary environmental threats to the basis of one of the central images of their mythology.